EXPECTATIONS REGARDING AGING AMONG OFFSPRING OF CENTENARIANS. (11th November 2018) - Andersen, S; Cui, Q; Perls, T; Sebastiani, P
Abstract: Introduction: Negative views of aging are associated with poor health behaviors and increased mortality. As many centenarians have been shown to delay or escape age-related illnesses, we hypothesized that their offspring would have better views of aging than their peers and that this positivity towards aging would contribute to their lower demonstrated mortality. Methods: New England Centenarian Study participants (183 centenarian offspring and 144 birth cohort-matched individuals without parental longevity, mean age 73.2 ± 7.1 years) completed the Expectations Regarding Aging (ERA) questionnaire in 2006 and were followed annually for health and survival outcomes. We compared ERA scores between offspring and controls using linear regression adjusted for age, sex, and education. We used Cox proportional hazards models to evaluate the association of ERA with mortality. Results: We found no difference in ERA scores between offspring and controls (means 90.7 ± 19.3 and 90.7 ± 16.4 respectively, p=.34). Over 12 years of follow-up, 21% (N=38) of offspring and 35% (N=51) of controls died. Unadjusted survival analysis revealed a small, significant association of ERA score with mortality (hazard ratio 0.982, CI 0.971–0.993) and when covariates were added the effect of ERA disappeared and higher age (HR=1.123, CI 1.078–1.169) and impairments in IADL (HR=0.825, CI 0.727–0.935) were better predictors of mortality. Conclusion: Centenarian offspring do not have more positive views of aging than their peers. The benefit of positive views on aging in this cohort may have a lower influence upon their healthy aging and lower mortality rate compared to other factors such as healthy behaviors and genetic factors.